DEVELOPMENT OF TEST INSTRUMENTS BASED COMPUTER- HIGHER ORDER THINKING (CBT-HOT) IN INTERMEDIATE READING COURSES - PUSPARINI, INDRAWATI; PUSPITA SARI2, IKE DIAN (Linguists : Journal of Linguistics and Language Teaching, 2020)
This  research developed  product of test instruments based computer -High Order Thinking (CBT-HOT)  in intermediate reading courses in Ikip Budi Utomo Malang. Test instruments based computer -High Order Thinking (CBT-HOT) in intermediate reading courses are high-level test package that are provided online by using a website as a basis for students who access it, so it is suitable to campus vision that must use ICT technology. The product consists of five test packages compiled with high-level criteria according to Taxonomy Bloom , those are package A, B, C, D and E. The design of this research adapts from the Borg and Gall model with the following steps (1) need analysis, (2) planning, (3) product development, (4) expert validation, (5) product revisions and (6) product trials. The objectives of this study are: (1) to produce scientific articles published in reputable national journals; (2) to produce scientific article published in international scientific journals; (3) produce CBT-HOT based test computer products that will be certified. The average value on material validation showed good results,  which the average score 2,81. The average value of media  validation also shows good results, which is 2.86. The average value in test instruments is 2.87.